Transmisi Virus Covid-19 Dari Ibu Hamil Ke Janin : Systematic Literature Review - Claudia Leniensi; Catur Wulandari; Eka Vicky Yulivantina; Galuh Tunggal Prastiti (Journal of Health (JoH), 2021)
The number of patients with Covid-19 is on the increase, resulting in the cumulative and neonatal health. Goverments implement policies and handbill on the Covid-19 virus prevention and treatment efforts, including maternal and neonatal. People have also adopted government regulations. The methods in this study are literature review journals with types of literature review of PubMed, Google Scholar, and Cochrane. The sample of this research is a journal already made critical apprasial with inclusion and excretion criteria. Literature review shows a 2020 journal published internationally and for research design case report. Pregnant mother gave birth to sectio caesaria at 37 weeks of pregnancy. Mothers did a swab test (RT-PCR) to check diagnostics. Most babies are born to men with body weight born more than 2500 grams. All babies make self-contained isolation in good condition with over 7 at first and fifth minutes. Complications are certain, and swab inspection is made on nasofaring. A lab of the Covid-19 virus transmission from the pregnant mother to the fetus negative. The lab did not have a Covid-19 virus acid on the pacenta sample, blood but central, amniotic fluid, throat and feses. Results from a lab of a vertical transmission of the Covid-19 virus from a pregnant mother to a negative fetus.